PENGARUH PICTORIAL HEALTH WARNING TERHADAP INTENTION TO QUIT SMOKING DENGAN EVOKED FEAR SEBAGAI MEDIASI (Pada Mahasiswa Perokok Ringan Di Kota Pontianak) - B1021161037, REKSY RAY SANDY (Jurnal Manajemen Update, 2020)
The purpose of this study is to test and analyze the effect of Pictorial Health Warning on Intention to Quit Smoking with Evoked Fear as a mediation variable among light smoker students in Pontianak City. Respondents in the study were students who smoke lightly who live in Pontianak City. The sample in this study was 75 respondents using non-probability sampling as sampling techniques and the data analysis model used was Path Analysis. Data collection in this study was carried out by distributing questionnaires via online. The results of this study shows that pictorial health warning directly has a positive and significant effect on Intention to Quit Smoking and evoked fear is proven as a partial mediation or partially mediate the relationship between pictorial health warning and Intention to Quit Smoking. Keywords: Pictorial Health Warning, tobacco, evoked fear, and intention to quit smoking.DAFTAR PUSTAKAAditama, T.Y. (1997). Rokok dan Kesehatan. Edisi ke-3. Jakarta: Gramedia.Ajzen, I. (2005). Attitudes, Personality and Behavior. New York: Open University Press.Alaouie, H., et al. (2015). Effectiveness of Pictorial Health Warnings on Cigarette Packs among Lebanese School and University Students. Tobacco Control, 24, 12-16.Andrews, J, C., et al. (2016). Effects of plain package branding and graphic health warnings on adolescent smokers in the USA, Spain and France. Tobacco Control, 25, 120-126.Armstrong, S. (1991). Pengaruh rokok terhadap kesehatan. Jakarta: Arcan.Azzara, C. V. (2010). Questionneire Design For Business Research. USA: Tate PublisingBorland, R., et al. (2009). Impact of Graphic and Text Warnings on Cigarette Packs: Findings From Four Countries Over Five Years. Tobacco Control, 18, 358-364.Boudreaux, E. D., et al. (2010). Intentions to Quit Smoking: Causal Attribution, Perceived Illness Severity, and Event-Related Fear During an Acute Health Event. Annals of Behavioral Medicine, 40 (3), 350-355.Cameron, L.D., et al. (2013). Responses of Young Adults to Graphic Warning Labels for Cigarette Packages. Tobbaco control, 24(05), 14-22.Ciptono, F. (1997). Strategi Pemasaran Edisi I. Yogyakarta: Andi.Cunningham, R. (2014). Cigarette Package Warning Size and Use of Pictures: International Summary. Ottawa: Canadian cancer society.Darsono. (2012). Faktor Emosi dalam Perilaku Konsumen. Dharma Ekonomi, 1 (36), 1-11.Databoks. (2016). 1 dari 4 Pemuda Indonesia Merokok Setiap Hari. Diakses dari https://databoks.katadata.co.id/datapublish/2016/11/08/1-dari-4-pemuda-indonesia-merokok-setiap-hari.Databoks. (2019). Negara dengan Jumlah Perokok Terbanyak di Asean. diakses dari https://databoks.katadata.co.id/datapublish/2019/05/31/indonesia-negara-dengan-jumlah-perokok-terbanyak-di-asean. Donovan, R., & Henley, N. (2010). Principles and Practice of Social Marketing. United Kingdom: Cambridge University Press.Driezen, P., et al. (2016). Determinants of intentions to quit smoking among adult smokers in Bangladesh: findings from the International Tobacco Control (ITC) Bangladesh wave 2 survey. Global Health Research and Policy, 1 (11), 1-12.Fathelrahman, A. I., et al. (2010). Impact of The New Malaysian Cigarette Pack Warnings on Smokers' Awareness of Health Risks and Interest in Quitting Smoking. International Journal of Environmental Research and Public Health, 7 (11), 4089-4099.Ferdinand, A. (2002). Structural Equation Modelling dalam Penelitian Manajemen: Aplikasi Model-model Rumit dalam Penelitian untuk Tesis Magister dan Disertasi Doktor. BP UNDIP.Ghozali, I. (2011). Aplikasi Analisis Multivariate dengan Program SPSS. Semarang: Badan Penerbit Universitas Diponegoro.Goleman, D. (2002). Kecerdasan Emosional: Mengapa EI Lebih Penting Daripada IQ. Jakarta: Gramedia Pustaka Utama.Hamdan, S.R. (2015). Pengaruh Peringatan Bahaya Rokok Bergambar pada Intensi Berhenti Merokok. MIMBAR, 31 (1), 241-250.Hammar, H., & Carlsson, F. (2005). Smokers' expectations to quit smoking. Health economics, 14 (3), 257-267.Hammond, D. (2011). Health Warning Messages on Tobacco Products. Tobacco Control, 20 (5), 327–237.Hastings, G., Stead, M. & Webb, J. (2004). Fear Appeals in Social Marketing. Psychology & Marketing, 21 (11), 961- 986.Hoog, N.D., et al. (2005). The Impact of Fear Appeals on Processing and Acceptance of Action Recommendations. Personality and Social Psychology Bulletin, 31 (1), 24–33.Hou, M., & Zuohau, H. (2013). Patronage, Only for Happiness? an Analysis on Coexistence of Multiple Consumption Emotions. Business and  management Research, 2 (1), 109-116.Irawan, H.D. (2009). 10 Prinsip Kepuasan Pelanggan. Edisi Kedua. Jakarta: Elex Media Komputindo.Jogiyanto. (2007). Sistem Informasi Keperilakuan. Edisi Revisi. Yogyakarta: Andi.Jung, M. (2016). Implications of Graphic Cigarette Warning Labels on Smoking Behavior. Journal of Cancer Prevention. 21 (1), 21-24.Kees, J., et al. (2010). Understanding How Graphic Pictorial Warnings Work on Cigarette Packaging. Journal of Public Policy & Marketing, 29 (2), 265 –276.Kementrian kesehatan RI. (2013). Peraturan Menteri Kesehatan RI Nomor 28 Tahun 2013 tentang pencantuman peringatan kesehatan dan informasi kesehatan pada kemasan produk tembakau.Kotler, P. (2005). Manajemen Pemasaran. Jilid 2. Edisi kesebelas. Jakarta: Indeks.Kotler, P., & Keller, K.L. (2013). Manajemen Pemasaran, Jilid Kedua. Jakarta: Erlangga.Kotler, P., & Nancy R. L. (2008). Social Marketing: Influencing Behaviors for Good. California: Sage Publications Inc.Linanda, D., et al. (2017). The Effect of Fear Appeals Advertisement and Health Social Messages on The Intention of Smoking Cessation. Jurnal Ilmiah Psikologi MANASA, 6 (2), 127-130.Mannocci, A. (2014). Demographic Characteristics, Nicotine Dependence, and Motivation to Quit as Possible Determinants of Smoking Behaviors and Acceptability of Shocking Warnings in Italy. Journal of Biomedicine and Biotechnology, 14 (5), 1-10.Morvan, K.G. (2013). Plain Packaging and Public Health: The Case of Tobacco. Journal of Business Research, 3 (66), 133–136.Mowen, J., & Minor, M. (2002). Perilaku konsumen, jilid 2. Jakarta : Erlangga.Mubarak. (2014). Studi Kontribusi Faktor Determinan Intensi Merokok dalam Rangka Pencegahan Perilaku Merokok. Prosiding Sosial, Ekonomi, dan Humaniora, 4 (1), 36-46.Muhibbin, S. (2010). Psikologi Pendidikan dengan pendekatan baru. Bandung: PT Remaja Rosdakarya.Mustafa, Z. Q. (2009). Mengurai Variabel Hingga Instrumentasi. Yogyakarta: GrahaIlmu.Prawitasari, J.E. (1995). Stres dan Kecemasan Pengertian Manifestasi dan Penanganannya. Yogyakarta: Bulettin Psikologi..Rini, E.S., & Absah, Y. (2015). Analisis Penciptaan Loyalitas Melalui Pengaruh Penerapan Strategi Pemasaran Rasional, Emosional,dan Spiritual Terhadap Kepuasan. Jurnal Studi Manajemen dan Bisnis, 2 (1).Sanjaya, D.S., & Kusasih, I.A.K.R., (2012). Pengaruh Fear Appeals, Endorser dan Jingle dalam Iklan Suzuki Nex di Televisi Versi Band Smash terhadap Respon Konsumen. Jurnal Graduasi, 28, 59 – 70.Schiffman., & Kanuk. (2008). Perilaku konsumen. Edisi 7. Jakarta: Indeks.Sekaran, U., & Bougie, R. (2017). Metode Penelitian untuk Bisnis Pendekatan Pengembangan-Keahlian. Edisi 6 Jilid 2. Jakarta: Salemba Empat.Siegel, M. (2002). Antismoking Advertising: Figuring Out What Works. Journal of Health Communication, 7, 157-62.Smadi, M.O. (2012). Factors Affecting Adoption of Electronic Banking. International Journal and Business and Social Science, 3 (17), 294-309.Solimun. (2011). Analisis Variabel Moderasi dan Mediasi. Malang: FMIPA Universitas Brawijaya..Sugiyono. (2017). Metode Penelitian Bisnis Pendekatan Kuantitatif, Kualitatif, Kombinasi, dan R & D. Bandung: Alfabeta.Sunyoto, D. (2012). Dasar-dasar Manajemem Pemasaran. Yogyakarta: Penerbit Caps.Taghilou, S., & Hanzaee, A.H. (2017). The Effect of Background Color and Level of Threat on Evoked Fear and Smoking Cessation Intentions. Palma Journal, 16 (3), 1-7.Wauters, B., Brengman, M., & Mahama, F. (2014). The Impact of Pleasure-Evoking Colors on the Effectiveness of Threat (Fear) Appeals. Psychology & Marketing, 31 (12), 1-13.Wells, et al. (2000). Advertising: principles & practice. Fifth edition. New Jersey: Prentice Hall International Inc.Wigg, S., & Stafford, L.D. (2016). Health Warnings on Alcoholic Beverages: Perceptions of the Health Risks and Intentions towards Alcohol Consumption. PLOS ONE, 11 (4).Yong, et al. (2013). Adult Smokers’ Reactions to Pictorial Health Warning Labels on Cigarette Packs In Thailand and Moderating Effects of Type of Cigarette Smoked: Findings From The International Tobacco Control Southeast Asia Survey. Nicotine & Tobacco Research, 15 (8), 1339–1347.Zadegan, et al. (2004). Tobacco Use Among Iranian Men, Women and Adolescents. European Journal Of Public Health, 2 (14), 76–78.Zeithaml, et al. (2006). Service marketing. McGraw-Hill international edition.Zhao, et al. (2010). Reconsidering Baron and Kenny: Myths and Truths about Mediation Analysis. Journal of Consumer Research,inc. (37), 197-206.